Penyuluhan Gizi Seimbang Melalui Edukasi Bijak Mengonsumsi Makanan Cepat Saji pada Anak Panti Asuhan Natasya Liora Kasih Indonesia - Pricilia, Yolanda; Suci, Delli; Conia, Astri; Amelia, Fatma; Ms, Yusnadi; Subaedah, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to provide education on balanced nutrition and the impact of fast food consumption on children at the Natasya Liora Kasih Indonesia Orphanage. The method used is descriptive qualitative with data collection techniques through observation, interviews, questionnaires. The subjects in this study were children aged 8-17 years who lived in the orphanage, with a total of 15 participants. The sample was selected purposively by considering their active involvement in counseling activities. Data analysis used a descriptive qualitative analysis model. The results showed that before the counseling, children had a low understanding of balanced nutrition and tended to consume fast food without considering its impact. After being given community-based nutrition education, there was an increase in children's understanding of the importance of a healthy diet and changes in food selection habits. This counseling also received a positive response from the orphanage manager who realized the importance of providing nutritious food for children. These findings indicate that interactive and practice-based nutrition education can be an effective strategy in increasing awareness of healthy eating patterns in orphanage environments.